The influence of the use of the SiANEH application on mothers’ independence in monitoring the growth and development of toddlers - Siregar, Nilda Yulita; Sembiring, Arihta Br.; Nasution, Eva Mahayani; Kurnia, Herni; Siregar, Siti Julianita Siregar (Media Penelitian dan Pengembangan Kesehatan, 2026)
Background: Stunting is a significant health issue in Indonesia, affecting children's physical and cognitive development, as well as their future quality of life. One key strategy for preventing stunting is ensuring optimal monitoring of toddlers' growth and development. Objective: This study examined the impact of the Android application "SiANEH" on monitoring growth, development, and stimulation, aiming to improve mothers' independent practices in stunting prevention efforts in Kutalimbaru Village, Deliserdang Regency. Methods: A quasi-experimental design with a quantitative analytical approach was used, specifically a one-group pretest-posttest design. The research was conducted in Kutalimbaru Village, with a sample of 30 mothers of toddlers selected via purposive sampling. The study measured mothers' independent practices in monitoring growth and stimulating toddlers, utilizing the "SiANEH" app, which provides information on child development and reminders for stimulation. Data were collected through observation and completion of observation sheets. The research instruments were validated for content and reliability before application, and ethical approval was obtained from the Health Research Ethics Committee of Poltekkes Kemenkes Medan. Results: The results revealed a positive and significant effect of the "SiANEH" app on child growth monitoring (r=0.532, p= 0.002), child stimulation (r=0.790, p= 0.000), and maternal independence in monitoring and stimulation (r=0.534, p= 0.002). Pretest scores for growth monitoring (1.57) and stimulation (1.60) increased significantly in the posttest (3.40 and 3.70, respectively), as did maternal independence (from 1.80 to 3.60). Conclusion: These findings indicate that the "SiANEH" application enhances mothers' involvement in independently monitoring and stimulating child development, contributing to stunting prevention.